Beyond Oil Prices: A Comparative Analysis of the Indirect Effects of Energy Prices on Economic Growth in Türkiye and Russia - Abdallah Abukalloub; Dilara Berrak TARHAN; Ayşe GÜNGÖR (Salus Publica: Journal of Community Service, 2026)
This study examines the impact of energy prices on economic growth through a comparative analysis of Türkiye and Russia. The analysis uses annual data covering the period 2000-2024. The primary empirical assessment employs a multiple linear regression (OLS) model, with panel data techniques used as complementary methods to analyze long-run relationships and test the robustness of the findings. Brent crude oil prices are used as a proxy for energy prices, and the GDP growth rate serves as the indicator of economic growth. Unemployment, inflation, exchange rate, trade volume, and gross capital formation are included in the model as control variables. The findings indicate that Brent oil prices have a negative and statistically significant effect on economic growth. Moreover, the adverse effects of unemployment and exchange rate fluctuations on growth are stronger, whereas gross capital formation contributes positively to economic growth. The results of the interaction model reveal that the effect of oil prices does not differ significantly between the two countries. In conclusion, the impact of energy prices on economic growth is not direct but is shaped by macroeconomic conditions and varies with country-specific structural characteristics.